Research on the Pulsed Magnetic Field Device for Sterilization of Fruit and Vegetable Equipment - Liu Mingdan; Chen An Jun; Wang Yong; Tan Pengfei; Zhao Sifen (Institute of Advanced Engineering and Science, 2013)
In view of the requests of the sterilization device of the fruit and vegetable that integrate cleaning and juicing together, and combined with the electromagnetic theory and the cold sterilization technology which is in common use in modern food industry, circuits are designed for the pulsed magnetic field sterilization device of the integrated machine .This circuits chose a linear solenoid in which r= 30mm, l= 200 mm. The experiment shows that the pulsed magnetic field produced by the device can achieve a better effect in killing bacillus coli, beer yeast and staphylococcus aurous, etc. Compared with the traditional sterilization device, the bactericidal effect of the pulsed magnetic field sterilization device is more obvious so that it will be the direction of the development of food equipments. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2388